Effect of interalated lithium on electronic structure of talc - Балабан, Оксана Василівна; Лукіянець, Богдан Антонович; Сиротюк, Степан Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
In order to characterize the process of intercalation the electronic states (partial and total density of states) of talc, the Fermi level, the potential energy minima are evaluated within the projector augmented wave method (PAW). It is shown that the p-states of O mainly form the valence band while s- states of Si, O, Мg mainly form the conduction band of the talc. The calculated band gap is 5,08 еV. Total energy of the talc with the penetrated lithium into these minima is analyzed. It is obtained that the thermodynamically stable state of the talc/Li system is realized with lithium in the van der Waals gap of the talc structure. This fact coincides with experimental data according to which a guest penetrates exactly into the van der Waals gap during intercalation process. The lithium atom intercalated into the minima of the initial talc potential energy causes the reduction of the band gap and increase in the Fermi energy. These results will be used in the industrial production of batteries.